STUDI KASUS : PENERAPAN TEKNIK MARMET SEBAGAI UPAYA MENINGKATKAN PRODUKSI ASI IBU POST PARTUM - Lestaluhu, Viqy (Jurnal Kebidanan, 2025)
Optimal breast milk production during the postpartum period is crucial for achieving exclusive breastfeeding. However, many mothers experience difficulty meeting their babies' milk needs due to physiological and psychological barriers, such as stress, inappropriate breastfeeding techniques, and lack of breast stimulation. One non-pharmacological approach that can be used to help increase breast milk production is the Marmet technique, a combination of breast massage and manual expression aimed at facilitating milk flow and stimulating the oxytocin reflex. This case study aims to illustrate the effectiveness of the Marmet technique in increasing breast milk production in postpartum mothers. The subject was a postpartum mother who experienced decreased breast milk production in the early stages of breastfeeding. The intervention was carried out for two weeks, regularly applying the Marmet technique before breastfeeding and before expressing breast milk. Data were collected through observations of breastfeeding frequency and the increase in expressed breast milk volume. The results showed a gradual increase in breast milk production after the intervention, characterized by an increase in expressed volume and a reduction in complaints of breast tenderness. In addition, the mother also reported increased comfort and confidence during breastfeeding. These findings suggest that the Marmet technique can be a simple and effective alternative intervention to address breast milk production issues in postpartum mothers. This study confirms that implementing the Marmet technique can support successful exclusive breastfeeding.